(untitled) (Research, Society and Development, 2023)
Perinatal palliative care (PPC) is promoted by a multidisciplinary team and seeks to improve the quality of life of the newborn (NB) with serious illness. The present study aims to analyze published research on fetal palliative care in the period from 2017 to 2022. Integrative literature review conducted in the Virtual Health Library. The descriptors were "palliative care" and "fetal". It was found that the family and professionals involved with a problematic pregnancy develop negative feelings due to the unpreparedness of doctors to communicate bad news. Communication of a somber fetal diagnosis should be empathetic, objective, and truthful in order to assist the family in decision making. Given the diagnosis, a follow-up pregnancy plan should be made, aiming to reduce unnecessary interventions. Perinatal care decisions should be made by the parents with advice from the team. After delivery, the family should be welcomed and oriented about the adoption of palliative care. The measures to be taken in the PPC are individualized, as they depend on the diagnosis and prognosis of the baby. The multidisciplinary team in the care of the NB and their families can offer support for early mourning. Therefore, the relevance of PPC was demonstrated to welcome the family and avoid dysthanasia. The need for further research to understand the situation of fetal PPC nationwide was perceived. Furthermore, it is essential to promote more training of health care teams, including physicians and medical students, in order to improve communication of bad news and palliative care.